Integration of Big Data and Artificial Intelligence in Constructing Learners' Individualized Feedback System - Chen, Jingchun; B.D., Parameshachari (2023 International Conference on Data Science and Network Security (ICDSNS), 2023)
The evolution of Artificial Intelligence (AI) systems has led to the emergence of different feedback methods in L2 writing. However, it is not clear how these alternative feedback methods can enhance writing quality and how they fit into the broader context of writing instruction. To address this issue, AI-based feedback system has been proposed as a potential solution in this study. It is the application of artificial intelligence technology in language writing. The feedback system is composed of front-end learning unit and back-end support unit. In multi-manuscript writing, the intelligent feedback system provides feedback in the aspects of text structure, context, style and rhetoric, which has certain significance to improve the quality of writing proficiency. The study involved 65 intermediate Chinese second language learners, they were divided into experimental and control groups. The experimental group received feedback with the help of the system by completing a multi-draft essay writing task. The findings revealed that learners in experimental group made the most accurate essay-writing task and they preferred the application of this feedback system. Learners acknowledged the potential benefits and drawbacks of using this system in producing high-quality writing. The study indicated that this AI-based feedback system will significantly improve learners' overall writing gains and the learning engagement.